2018
DOI: 10.1002/ps.4849
|View full text |Cite
|
Sign up to set email alerts
|

AHAS Trp574Leu substitution in Raphanus sativus L.: screening, enzyme activity and fitness cost

Abstract: This is the first report of fitness cost associated with the AHAS Trp574Leu mutation in R. sativus populations. This fitness cost could reduce frequency of the resistant allele without herbicide selection. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(71 citation statements)
references
References 35 publications
6
65
0
Order By: Relevance
“…In a previous study, AHAS-resistant feral radish carrying the Trp574Leu mutation showed negative pleiotropic effects on AHAS activity and reproductive traits under intraspecific interference 19 . However, the lack of information of fitness costs associated with the Trp574Leu mutation in different life-history traits of feral radish and under crop interference limits the development and implementation of evolution-knowledge-based resistance management strategies .…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…In a previous study, AHAS-resistant feral radish carrying the Trp574Leu mutation showed negative pleiotropic effects on AHAS activity and reproductive traits under intraspecific interference 19 . However, the lack of information of fitness costs associated with the Trp574Leu mutation in different life-history traits of feral radish and under crop interference limits the development and implementation of evolution-knowledge-based resistance management strategies .…”
Section: Introductionmentioning
confidence: 84%
“…The first AHAS-resistant feral R. sativus population reported in Argentina was used in this study 2,19,22 . Recently evolved AHAS-resistant plants carrying the Trp574Leu mutation were collected in the south of Buenos Aires province, in a field planted with IMI-resistant oilseed rape after imazethapyr application by the farmer 19,22 .…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…). Several works showed that herbicide resistance‐endowing AHAS gene mutations result in decreased AHAS activity in dicots . Increased or unchanged AHAS activity has been observed for a number of resistance mutations in other species .…”
Section: Discussionmentioning
confidence: 99%